Are Global Managers Able to Deal with Work Stress - Belal Barhem (Journal of Accounting, Business and Management (JABM), 2008)
The study seeks to understand the extent to which private sector managers are responding to demands and expectations of globalization and what the sources are of their work stress. Are they equipped with the necessary skills to deal with globalization and the challenges at work? The paper also examines the degree to which the participants sampled have the characteristics which would enable them to work globally, such as how they view other people's values and how far they can adapt to new working environments? A sample of 196 managers from the private sector in the U.A.E. was involved in the study. The study reveals that global characteristics are significantly exhibited among managers in the private sector. With broad responsibility for others, private managers consider the most important sources of work stress are role ambiguity and role overload (of a qualitative kind). Some managerial implications were proposed.